Analisis Model Bisnis dan Manajemen Operasional Perusahaan Start-up E-Commerce - Retno Ayu Puspita S; Ramlawati; Serlin Serang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to further review how the business model and operational management of e-commerce start-up companies. This type of research uses a qualitative approach. With the library research method, namely research whose object of study uses library data in the form of books as its data source. The results of this study show that in the start-up-commerce business model, startups facilitate the process of purchasing and delivering goods or services through a website or application. A successful e-commerce business model usually focuses on forming strong relationships, utilizing technology and being able to innovate. The operational management of start-up companies is by increasing brand awareness through social media as a marketing channel.